2022
DOI: 10.21608/jfds.2022.159339.1071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pan Bread Fortified with Sunflower Seeds Powder

Abstract: The main goal of such work was to study the effect of adding sunflower seeds powder in different ratios (5, 10, 15 and 20%) on chemical composition, amino acids contents, fatty acids composition, rheological properties, physical features, bioactive compounds and sensory evaluation of pan bread samples. The obtained results indicated that sunflower seeds powder contained 12.79% crude protein, 24.98% oil, 35.98% crude fibers and 3.53% ash contents. Also, sunflower seeds powder were rich in Ca (191.16 mg/100g), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
0
1
Order By: Relevance
“…And Dou et al [79] who found that n-3 poly unsaturated fatty acids could slightly enhance the level of bone mineral density, more significant for postmenopausal women increased effect on bone mineral density. On the other hand, our results differences with Albahlol et al [60] who stated that wheat flour fortified with sun flower flour to produced bread led to high total saturated fatty acids value and low unsaturated fatty acids with increased sun flower flour level.…”
Section: Fatty Acids Composition Of Selected Pan Breadcontrasting
confidence: 99%
See 1 more Smart Citation
“…And Dou et al [79] who found that n-3 poly unsaturated fatty acids could slightly enhance the level of bone mineral density, more significant for postmenopausal women increased effect on bone mineral density. On the other hand, our results differences with Albahlol et al [60] who stated that wheat flour fortified with sun flower flour to produced bread led to high total saturated fatty acids value and low unsaturated fatty acids with increased sun flower flour level.…”
Section: Fatty Acids Composition Of Selected Pan Breadcontrasting
confidence: 99%
“…In the same Table, our results arein agreement with these of De Lamo and Gómez [59] who found that sun flower carbohydrate 24.07% but differences in protein 19.33%, lipid 49.8%, fiber 9%, energy value 582kcal/100g, and water 1.2g/100g. Our results are in agreement with these of Albahlol et al [60] who found that sun flower seeds flour moisture, protein, ash and carbohydrates (5.85%, 12.79%, 3.53% and 22.72% respectively) but differences in % fat and % fiber content (24.98 % and 35.98% respectively).…”
Section: Chemical Composition Of Raw Materialssupporting
confidence: 94%
“…Using catechin as the standard, the concentration was calculated using a calibration curve. Catechin equivalents (CE) were expressed as mg of CE/g fresh weight [29].…”
Section: Analysis Of the Plant Extracts' Anti-oxidant Activity (Aoa)mentioning
confidence: 99%